The Contextual Qur’anic Interpretation of Jihad - Kumala, Nur (Aqwal: Journal of Qur'an and Hadis Studies, 2021)
In the 20th century, Indonesia was faced with issues of right-wing extremism in the name of religion which affected the benefit of the people. Several acts of terror, the discourse of the caliphate, returning to the sunnah, and dictation of takfiri have become the center of topics in our country, where the issue of "jihad" against religion and the state is often misinterpreted in a harsh and coercive way. Thus, through analyzing the contemporary interpretation of the Double Movement, the interpretation of the verse is more inclined towards more universal values, which are humanist, freedom (al-hurriyah), equality (al-musawwah) and justice (al-'adalah). So that it produces some understanding that jihad is not just about war, but can be done in various ways by looking at the contextuality of the times, as in the viewpoint of Habib Lutfi, that defending the country and homeland as the term "jihad today" is one of the alternatives in silencing the understanding. “Conventional jihad” brought about by elements in destroying religion and the state, including strengthening knowledge of history, increasing the achievement of the nation's children and understanding of ukhuwah wathaniyah which are interconnected to silence as a form of love for the homeland and jihad for the advancement of religion and the state.